When Territoriality Meets Agency: An Examination of Employee Guarding as a Territorial Strategy. (September 2018) - Gardner, Timothy M.; Munyon, Timothy P.; Hom, Peter W.; Griffeth, Rodger W.
Do managers behave territorially toward their employees? Despite accumulating evidence demonstrating the prevalence of territoriality over nonagentic organizational resources, key questions remain regarding the extent to which psychological ownership and territorial behavior occur within supervisor-subordinate relationships. To explore this question, we drew on territoriality and mate-guarding theory to ascertain how and why managers might utilize one form of territoriality, anticipatory defenses, toward their employees. In a four-study investigation, we find that managers consistently engage in two forms of anticipatory defense tactics, persuasion and nurturing, that are intended to defend ownership claims over their employees and limit employee defection. Our results demonstrate a positive relationship between psychological ownership of subordinates and employee guarding directed toward those subordinates. We also find that managers engage in employee guarding more when they anticipate an employee is likely to defect, and they adapt guarding tactics in response to the subordinate's general mental ability. Collectively, our results identify the motivations and conditions under which supervisors act territorially toward agentic subordinates, contributing to theory in territoriality and downward social influence.